O desafio da construção das marcas: proposta de um modelo - Oliveira, Elaine Ribeiro de (2017)
According to the current global economic scenario, marked by hypercompetitiveness, marketing managers have faced great challenges in building strong brands. Whereas, the permanence of trademarks depends on the use of effective and innovative strategies, which are inserted and based on relevant models. In order to do so, it’s also important to consider socioeconomic and cultural issues that have become relevant to brand managers, given their complexity among social actors and the multiplicity of value that further challenges marketing managers. In this premise, this thesis has as its main theme: " The challenge of brand building: Proposal of a model ", which inspires new perspectives for the management and marketing field, and aim to contribute to brand theory and management, in order to elucidate the gaps in the models presented by the authors Aaker and Joamchimstaler (2007) and Keller (2013). In this perspective, the study sought to explore and achieve the goal of proposing a brand building model, in which is presented a research based on a methodological approach, a qualitative study, having as empirical verification strategy the method of study of multiple cases, Through the analysis of Arezzo and Schutz brands. Thus, one can perceive the relevance of the proposed model, after analyzing the content used in the interpretation of the results of the research carried out in this thesis